Beyond symptomatic relief for chemotherapy‐induced peripheral neuropathy: Targeting the source. Issue 11 (20th February 2018) - Ma, Jiacheng; Kavelaars, Annemieke; Dougherty, Patrick M.; Heijnen, Cobi J.
Abstract : Chemotherapy‐induced peripheral neuropathy (CIPN) is a serious adverse side effect of many chemotherapeutic agents, affecting >60% of patients with cancer. Moreover, CIPN persists long into survivorship in approximately 20% to 30% of these patients. To the authors' knowledge, no drugs have been approved to date by the US Food and Drug Administration to effectively manage chemotherapy‐induced neuropathic pain. The majority of the drugs tested for the management of CIPN aim at symptom relief, including pain and paresthesia, yet are not very efficacious. The authors propose that there is a need to acquire a more thorough understanding of the etiology of CIPN so that effective, mechanism‐based, disease‐modifying interventions can be developed. It is important to note that such interventions should not interfere with the antitumor effects of chemotherapy. Mitochondria are rod‐shaped cellular organelles that represent the powerhouses of the cell, in that they convert oxygen and nutrients into the cellular energy "currency" adenosine triphosphate. In addition, mitochondria regulate cell death. Neuronal mitochondrial dysfunction and the associated nitro‐oxidative stress represent crucial final common pathways of CIPN. Herein, the authors discuss the potential to prevent or reverse CIPN by protecting mitochondria and/or inhibiting nitro‐oxidative stress with novel potential drugs, including the mitochondrial protectant pifithrin‐μ, histone deacetylase 6 inhibitors, metformin, antioxidants, peroxynitrite decomposition catalysts, and anti‐inflammatory mediators including interleukin 10. This review hopefully will contribute toward bridging the gap between preclinical research and the development of realistic novel therapeutic strategies to prevent or reverse the devastating neurotoxic effects of chemotherapy on the (peripheral) nervous system. Cancer 2018;124:2289‐98 . © 2018 American Cancer Society . Abstract : Herein, the authors review current knowledge concerning the pathophysiological mechanisms underlying chemotherapy‐induced peripheral neuropathy, with a focus on mitochondrial dysfunction, nitro‐oxidative stress, and neuroinflammation. On the basis of these proposed mechanisms, they describe potential novel avenues for the development of mechanism‐based therapeutic strategies to prevent or reverse chemotherapy‐induced peripheral neuropathy that do not interfere with the antitumor effects of chemotherapy.